Peningkatan Aktivitas Belajar Matematika Melalui Model Pembelajaran Kooperatif Tipe Two Stay Two Stray (TSTS) (PTK Pada Siswa Kelas VII F SMP Negeri 1 Colomadu Semester Gasal Tahun Ajaran 2015/2016) - Ibnu Faiz Rijal, Al Faruq (2016)
This research aims to improve mathematics learning activities through cooperative learning methods type Two Stay Two Stray (TSTS). This type of research is a Classroom Action Research (CAR). The subjects of this study were teachers and students act as a conduit of class VII F SMP Negeri 1 Colomadu the 36 students as recipients of action. Methods of data collection using interviews, observation, field notes, test and documentation. Research data analysis technique is done by covering the stage of data collection, data reduction and data verification. The validity of the data is done by triangulation of sources and triangulation techniques. Results of the study can be seen from the following indicators: (1) Activity student in learning activities prior notice when the action as much as 10 students (27.78%), after the action to 31 students (86.11%); (2) Activity of students in asking questions before the action as much as 7 students (19.44%), after the action to 26 students (72.22%); (3) Activity student in an opinion prior to the action as much as 4 students (11.11%), after the action to 27 students (75%); (4) Activity student in front of the class before working on the action as much as 5 students (13.89%), after the action to 29 students (80.56%). From the indicator results of these studies, it was concluded that the implementation of cooperative learning model type Two Stay Two Stray (TSTS) can improve mathematics learning activities.